2013
DOI: 10.1371/journal.pgen.1003539
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalis Prophage Dynamics and Contributions to Pathogenic Traits

Abstract: Polylysogeny is frequently considered to be the result of an adaptive evolutionary process in which prophages confer fitness and/or virulence factors, thus making them important for evolution of both bacterial populations and infectious diseases. The Enterococcus faecalis V583 isolate belongs to the high-risk clonal complex 2 that is particularly well adapted to the hospital environment. Its genome carries 7 prophage-like elements (V583-pp1 to -pp7), one of which is ubiquitous in the species. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
175
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(184 citation statements)
references
References 90 publications
(130 reference statements)
6
175
1
2
Order By: Relevance
“…E. faecalis strain V583 is polylysogenic for 7 prophage-like elements (termed V583-pp1 to V583-pp7) ( Table 1). It was shown that three of these, pp1, pp4, and pp6, are important for adhesion to human platelets, which is possibly achieved by expression of the genes encoding PblA and PblB which are homologous to those of S. mitis (84). Thus, these examples nicely reveal that SPI triggered lysis of a small fraction of cells, possibly promoting the adhesion of the remaining noninduced part of the population.…”
Section: Spontaneous Prophage Activity Promotes Host Virulencementioning
confidence: 93%
“…E. faecalis strain V583 is polylysogenic for 7 prophage-like elements (termed V583-pp1 to V583-pp7) ( Table 1). It was shown that three of these, pp1, pp4, and pp6, are important for adhesion to human platelets, which is possibly achieved by expression of the genes encoding PblA and PblB which are homologous to those of S. mitis (84). Thus, these examples nicely reveal that SPI triggered lysis of a small fraction of cells, possibly promoting the adhesion of the remaining noninduced part of the population.…”
Section: Spontaneous Prophage Activity Promotes Host Virulencementioning
confidence: 93%
“…Hemodynamic non-responders to secondary FLT should be considered earlier for TIPS. Preliminary, albeit uncontrolled, data indicate that allocation of these patients to TIPS reduces rebleeding rate and bleeding-associated mortality [5, 97,106,[110][111][112][113].…”
Section: Tips Is Not Indicated For the Prophylaxis Of First Variceal mentioning
confidence: 99%
“…The inner plot visually describes with vertical blue lines the location and importance of antisense organizations detected (see the ppRNome browser for details). On the chromosome, the pathogenicity island (red) and other mobile genetic elements are annotated on the chromosome, i.e., efaC1/C2 (dark green), vancomycin resistance region (orange), and the six prophages (bright green) (Lepage et al 2006;Matos et al 2013). …”
Section: Motif Detection and Promoter Features In The E Faecalis Genomementioning
confidence: 99%